A Reliable Surgical Procedure for Sinus Floor Augmentation with Antral Pseudocysts - Yasuhiro Nosaka; Hitomi Nosaka; Yasushi Nakajima; Tadasuke Tanioka; Daniele Botticelli; Shunsuke Baba (Dentistry Journal, 2021)
An antral pseudocyst (AP) is a common well-defined ‘dome-shaped’ faintly radiopaque lesion of the maxillary sinus, and usually does not require treatment in asymptomatic patients. However, when sinus floor augmentation is required to increase bone volume for implant installation, the elevation of the sinus mucosa might drive the AP against the ostium. This might cause its obstruction and, as possible consequence, sinusitis. The purpose of this study was to investigate the clinical and tomographic conditions of APs to identify a predictable cyst removal that might allow a safety sinus floor augmentation. A total of 52 maxillary sinuses in 46 patients (mean age 55.1 years) presenting AP were examined by cone beam computed tomographies (CBCTs). A two-stage approach was applied. At the first surgery, the cystic lesions were further inspected by an endoscope through the antrostomy, and histopathological diagnosis of the removed tissues was carried out. After the confirmation of decrease of the swelling of sinus membrane by CBCT, the sinus floor augmentation was performed, at least four months after cyst removal. The color and transparency of the 86 cystic lesions were classified into 4 types. The whitish transparent cysts were 34 (39.5%), the yellowish transparent cysts were 18 (20.9%), the dark purple transparent cysts were 8 (9.3%) and the milky-white opaque cysts were 26 (30.2%). The contents of the 60 (69.8%) transparent cysts were serous fluid, but those of milky-white cysts were composed of viscous or elastic soft tissues, and the aspiration of the contents was unsuccessful. The analysis of the preoperative CBCT did not provide certainty on the contents of the cystic lesions. All cystic lesions were diagnosed as AP, and an infection was identified in one AP, presenting marked infiltration of the inflammatory cells. Considering the difficulties of performing a correct diagnosis of the AP content by a CBCT analysis, the risk of failure of the surgery that creates severe afflictions to the patients, and the necessity of a histological evaluation of the cyst, a two-stage surgery appeared to be the most reliable procedure.